Evaluating three methods of the presentation of target stimuli when teaching receptive labels. (30th August 2020) - Wong, Elizabeth; Ferguson, Julia L.; Milne, Christine M.; Cihon, Joseph H.; Leaf, Justin B.; McEachin, John; Leaf, Ronald; Schulze, Kim; Rudrud, Eric
Abstract: Practice recommendations related to using discrete trial teaching (DTT) to teach receptive labels (i.e., auditory–visual conditional discriminations) for individuals diagnosed with autism spectrum disorder (ASD) have included the use of counterbalancing. Counterbalancing involves two major components: (a) ensuring that each stimulus in the set is targeted an equal number of times within each trial block and (b) rotating the stimuli in the array in a manner that evenly distributes the stimuli within the array in each position across a trial block. The purpose of the present study was to compare three varying approaches to the order and number of presentations of target stimuli (i.e., predetermined, constrained, and unconstrained) during a receptive language task using an adapted alternating treatment design with three individuals diagnosed with ASD. The results indicated that, for the three participants, the unconstrained condition was the most efficacious, followed by the constrained condition, and the predetermined condition was the least efficacious with respect to average sessions to reach the mastery criterion. The implications of the results with respect to best practices using DTT to teach receptive language are discussed.